Stomach Content Analysis of Pangasius polyuranodon from the Kampar Kiri and Kampar Kanan Rivers - Verawati Verawati; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractPangasius polyuranodon is one of freshwater fishes that inhabit in the Kampar Kiri (Mentulik) and Kampar Kanan (Teratak Buluh) River in Riau. Pangasius polyuranodon known as opportunist fish, but information on its stomach content is limited. A research has been conducted at October to November 2017 to understand the stomach content of this fish. Sampling  was conducted once/week for a month period. There were 88 fishes captured, but 15 of them had empty stomach and its cannot be used for stomach content analysis. The analysis was conducted using the gravimetric method. Stomach content was analyzed as a basis to calculate the Preponderance Index (PI). Result shown that the main food of the fish from the Kampar Kiri River was insect (PI 95%), the complementary food was plant (PI 4%), and the additional food was debris (PI 1%). The main food of the Kampar Kanan River was bivalve (PI 76%), the complementary food was human waste (PI 16%), and the additional food was insect (PI 3%), domestic waste (PI 3%), plant (PI 1,8%) and debris (PI 0,1%). Based on data obtained, this fish can be categorized as omnivore.Keywords: Pangasius polyuranodon, Stomach Content Analysis, Gravimetric, Mentulik and Teratak Buluh River.